The Zombie Renaissance in Popular Culture
XI, 226 p.
Keywords: This collection addresses the significant cultural phenomenon of the 'zombie renaissance' – the growing importance of zombie texts and zombie cultural practices in popular culture. The chapters examine zombie culture across a range of media and practices including films games, music, social media, literature and fandom.